VITAMIN D DEFICIENCY PANDEMIC, A REALITY OR AN OVER DIAGNOSIS? NEED TO RETHINK VITAMIN D DEFICIENCY CUT OFF LEVELS - Bibi, Afshan; Asif, Naveed; Haroon, Zujaja Hina; Ijaz, Aamir; Nawaz, Asif; Atif, Qurat Ul Ain (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine clinical decision limits (cut off points) for vitamin D deficiency based on secondary hyperparathyroidism.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted in the Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology (AFIP), from Dec 2016 to May 2017.Methodology: One hundred and sixteen subjects, aged 18 to 60 years, of either gender, with vitamin D levels less than 50nmol/L, were consecutively included in the study.Results: Serum 25(OH) D had inverse relation with plasma iPTH level (r=-0.597, p